An anthropologist among the historians and other essays - Cohn, Bernard. S. (New York : Oxford University Press, 1990)
On the civilization and socioeconomic conditions of India; articles
Includes notes.
Keywords: An anthropologist among the historians and other essays; India -- Civilization; India -- Social conditions